2016
DOI: 10.1088/1758-5090/8/1/014103
|View full text |Cite
|
Sign up to set email alerts
|

Towards artificial tissue models: past, present, and future of 3D bioprinting

Abstract: Regenerative medicine and tissue engineering have seen unprecedented growth in the past decade, driving the field of artificial tissue models towards a revolution in future medicine. Major progress has been achieved through the development of innovative biomanufacturing strategies to pattern and assemble cells and extracellular matrix (ECM) in three-dimensions (3D) to create functional tissue constructs. Bioprinting has emerged as a promising 3D biomanufacturing technology, enabling precise control over spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
175
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(184 citation statements)
references
References 185 publications
0
175
0
2
Order By: Relevance
“…The second slice showed that the precursors developed, and some newly generated topics indicating recent ideas and innovations [24]. This slice showed rather a development of matter sciences ("Chemistry" and "Materials sciences, Biomaterials"), than of medical applications [9]. Similarly, the raise of "engineering" sciences vouched for research on improving the technological aspect of 3D printing (such as scale and automation).…”
Section: Science Mapping With Wos Categories (Figure 2)mentioning
confidence: 98%
See 2 more Smart Citations
“…The second slice showed that the precursors developed, and some newly generated topics indicating recent ideas and innovations [24]. This slice showed rather a development of matter sciences ("Chemistry" and "Materials sciences, Biomaterials"), than of medical applications [9]. Similarly, the raise of "engineering" sciences vouched for research on improving the technological aspect of 3D printing (such as scale and automation).…”
Section: Science Mapping With Wos Categories (Figure 2)mentioning
confidence: 98%
“…Bioprinting as a tissue engineering tool is one of the most promising technologies for overcoming organ shortage [3][4][5][6][7][8]; and the level of publication on Bioprinting has been continuously increasing over the past decade. However, the spread of populist articles among on this technology could potentially lead public opinion to idealize its readiness [9]. This enthusiasm is perhaps encouraged with reports of nearing clinical applications, however, the final necessary step of testing via in vivo implantation is rarely mentioned in bioprinting publications [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In thermal, laser and piezoelectric inkjet, cell damage mainly results from the thermal heating during the printing process, whereas in extrusion bioprinting, compression forces and shear stresses generated during the printing causes damage to cells [120] . On the other hand, biocompatible hydrogels widely used for matrix materials of cell-laden bioinks or supporting materials of printed cells require solidification strategies, e.g., photo-crosslinking, in situ chemical crosslinking, physical crosslinking or shear-thinning [121][122][123][124] . Integration of those solidification methods into bioinks is challenging, particularly in case of cell-laden hydrogel bioinks where the hydrogel gelation process should minimize the potential damage of encapsulated cells [121][122][123]125,126] .…”
mentioning
confidence: 99%
“…On the other hand, biocompatible hydrogels widely used for matrix materials of cell-laden bioinks or supporting materials of printed cells require solidification strategies, e.g., photo-crosslinking, in situ chemical crosslinking, physical crosslinking or shear-thinning [121][122][123][124] . Integration of those solidification methods into bioinks is challenging, particularly in case of cell-laden hydrogel bioinks where the hydrogel gelation process should minimize the potential damage of encapsulated cells [121][122][123]125,126] . Particularly, UV-based photopolymerization reactions of bioactive hydrogels (e.g., gelatin, collagen, chitosan) are commonly coupled with bioprinting, employed either during the printing process [127] or after the deposition of bioinks [39] to produce stable 3D hydrogels with intricate architectures for cell encapsulation.…”
mentioning
confidence: 99%